1991
DOI: 10.1002/mrm.1910220248
|View full text |Cite
|
Sign up to set email alerts
|

31P spectroscopy of the human prostate gland in vivo using a transrectal probe

Abstract: Using a transrectal probe, good quality 31P magnetic resonance spectroscopy of the human prostate was performed safely, consistently, and in a reasonable amount of time (average of 60 min). Initial results indicate that transrectal 31P MRS has the ability to characterize the phosphorylated metabolites of normal, hyperplastic, and malignant prostates. This study demonstrated that malignant prostates are characterized by significantly decreased levels of phosphocreatine (PCr) and increased levels of phosphomonoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 22 publications
5
16
0
Order By: Relevance
“…The near absence of signals in the phosphodiester region in the 7 T MR spectra of the prostate was in marked contrast with the phosphodiester region of low field strength in vivo 31 P MR spectra (including prostate spectra) (4,5,35). Those showed a high and broad peak in the phosphodiester region, which was generally assigned to GPC and GPE together, that is, free cytosolic compounds.…”
Section: Fig 6 Effects Of Nuclear Overhauser Effect (Noe) Enhancemementioning
confidence: 75%
“…The near absence of signals in the phosphodiester region in the 7 T MR spectra of the prostate was in marked contrast with the phosphodiester region of low field strength in vivo 31 P MR spectra (including prostate spectra) (4,5,35). Those showed a high and broad peak in the phosphodiester region, which was generally assigned to GPC and GPE together, that is, free cytosolic compounds.…”
Section: Fig 6 Effects Of Nuclear Overhauser Effect (Noe) Enhancemementioning
confidence: 75%
“…The assignments of the 'H resonances were made based on a previous knowledge of the phosphorylated metabolites observed in the respective tissues (16)(17)(18) and by comparison of chemical shifts and coupling constants of resonances with published values of known compounds at the same pH (19)(20)(21)(22)(23)(24)(25). Where assignments were ambiguous, resonance identities were confirmed by the addition of known standards (Sigma Chemical Co., St. Louis, MO).…”
Section: Metabolite Identificationmentioning
confidence: 99%
“…"P NMR spectroscopy has been used to study phosphorylated metabolites in prostate cancer in animals and humans (13)(14)(15)(16). These initial studies suggested that the ratios of phosphocreatine ( PCr) and phosphomonoesters ( PME) to adenosine triphosphate ( ATP) may differ in BPH and prostate cancer compared to normal tissue.…”
Section: Introductionmentioning
confidence: 99%